Testing of Carbon Steel Pipe and Stainless Steel Duplex Pipes of Welding Joints : A Cost and Time Perspective - Alamsyah Alamsyah; Ryo Herlambang; Rodlian Jamal Ikhwani; Taufik Hidayat; Wardina Suwedy (Collaborate, 2023)
In the welding process, it is not uncommon for a defect or discontinuity to occur in the welding results. Common defects on the surface are undercut, concavity, incomplete penetration, spatter, burn-through, and mismatch. While defects in internal welds that are often found during testing are porosity, worm holes, slag inclusions, incomplete fusion, and cracks, To obtain pipeline results that comply with the specifications set by the welding engineer and ASME or ASTM standards, it is necessary to test surface cracks and inside cracks using the non-destructive test (NDT) method, namely the dye penetrant test and radiography test, to determine the results of welding at pipe joints. In addition, it is also necessary to know the time and cost required for each method in the testing process. The results of the radiography test and penetrant test on carbon steel pipe welding joints showed porosity welding defects 1 mm long. Weld defects in duplex stainless steel pipes were not found. Then the results of the total testing time using the radiography test take 18% longer than testing using the penetrant test. Furthermore, the total costs that need to be incurred during the test are found to be 2 3 times more expensive than the cost of the penetrant test.